Pengaruh Kompetensi dan Budaya Organisasi Terhadap Kinerja Pegawai Badan Narkotika Nasional Provinsi DIY - Yuliantoharinugroho, Yuliantoharinugroho; Mochamad Rofik; Nadia Nur Ainindita (Sekolah Tinggi Ilmu Bisnis Kumala Nusa Yogyakarta, 2025)
The success of achieving organizational goals is influenced by one important aspect, namely employee performance. Performance can be influenced by internal factors, namely competence, and external factors such as organizational culture. This study aims to analyze the partial and simultaneous influence of competence and organizational culture on employee performance at the National Narcotics Agency of the Special Region of Yogyakarta Province. Data collection techniques used were observation, literature study, questionnaires, and documentation. The population of this study was all ASN employees at the National Narcotics Agency of the Special Region of Yogyakarta Province, totaling 74 people, sampled by simple random sampling technique of 63 people. The analysis used was instrument testing, normality testing, multiple regression analysis, and hypothesis testing. From the study, the results obtained from competence partially have a positive effect on employee performance as evidenced by the value of 2.062 > 2.00030 and a Sig. value of 0.044 < 0.05. Organizational culture partially has a positive effect on performance as evidenced by the value of 3.080 > 2.00030 and a Sig. value of 0.003 < 0.05. Likewise, competence and organizational culture simultaneously have a positive influence on employee performance, as evidenced by the value of 17.253 > 3.15 and the significance value (Sig.) of 0.000 < 0.05.